ChemInform Abstract: Ferromagnetic Behaviour of Fe‐Doped ZnO Nanograined Films. Issue 41 (7th October 2014) - Straumal, Boris B.; Protasova, Svetlana G.; Mazilkin, Andrei A.; Tietze, Thomas; Goering, Eberhard; Schuetz, Gisela; Straumal, Petr B.; Baretzky, Brigitte
Abstract Review: 74 refs.